2013
DOI: 10.3892/or.2013.2299
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia cells demonstrate a different metabolic perturbation provoked by 2-deoxyglucose

Abstract: Abstract. The shift in energy metabolism from oxidative phosphorylation to glycolysis can serve as a target for the inhibition of cancer growth. Here, we examined the metabolic changes induced by 2-deoxyglucose (2-DG), a glycolysis inhibitor, in leukemia cells by metabolome analysis. NB4 cells mainly utilized glucose as an energy source by glycolysis and oxidative phosphorylation in mitochondria, since metabolites in the glycolytic pathway and in the tricarboxylic acid (TCA) cycle were significantly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
4
24
0
Order By: Relevance
“…Regarding the energetic metabolism, our results categorize the different AML cells with NB‐4 as a glycolytic cell line, as reported in some studies,49, 50, 51 HL‐60 cells mainly dependent on glycolysis12 and KG‐1 cells displaying a predominant OXPHOS metabolism. These results not only showed that 2 closely related cell lines, NB‐4 and HL‐60, present different energetic metabolism, but also that KG‐1 cells are mainly OXPHOS dependent, as reflected by the carbon flux through mitochondria for lactate production (Figure 1).…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the energetic metabolism, our results categorize the different AML cells with NB‐4 as a glycolytic cell line, as reported in some studies,49, 50, 51 HL‐60 cells mainly dependent on glycolysis12 and KG‐1 cells displaying a predominant OXPHOS metabolism. These results not only showed that 2 closely related cell lines, NB‐4 and HL‐60, present different energetic metabolism, but also that KG‐1 cells are mainly OXPHOS dependent, as reflected by the carbon flux through mitochondria for lactate production (Figure 1).…”
Section: Discussionsupporting
confidence: 79%
“…2‐DG is taken up by glucose transporters (mostly GLUT1/3) and subsequently phosphorylated in 2‐deoxy‐ d ‐glucose‐6‐phosphate (2‐DG‐6P), which cannot be converted into fructose‐6P by phosphoglucose isomerase . This leads to a reduction in glucose metabolism through the glycolytic pathway and to the alternative shunting through the PPP associated with increased NADPH levels . Because NADPH is the cofactor of 5α‐R, the rate‐limiting enzyme of neurosteroid biosynthesis, its activation may increase the levels of neurosteroids that, in turn, directly activate extrasynaptic GABA A receptors, as reported previously …”
Section: Resultsmentioning
confidence: 54%
“…10 This leads to a reduction in glucose metabolism through the glycolytic pathway and to the alternative shunting through the PPP associated with increased NADPH levels. [11][12][13] Because NADPH is the cofactor of 5a-R, the rate-limiting enzyme of neurosteroid biosynthesis, its activation may increase the levels of neurosteroids that, in turn, directly activate extrasynaptic GABA A receptors, as reported previously. 22 Thus, we investigated whether the increase in the GABA A receptor-mediated outward current induced by 2-DG depends on the enhanced neurosteroid biosynthesis due to an increased availability of NADPH.…”
Section: Inhibition Of Neurosteroidogenesis Suppresses the 2-dginducementioning
confidence: 65%
See 2 more Smart Citations